Crow’s index in the population of Crimean Tatars - Атраментова, Л. О.; Мустафаєва, Л. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The parameters of natural selection in Crimean Tatars are typical for modern populations. They are characterized by a much higher index of differential fertility in comparison with the index of differential mortality at a relatively small value of the index of total selection. For one generation the total selection index Itot in the Crimean Tatars population has decreased from 0,37 to 0,25. Specific weight of Im component, which is due to differential mortality, in the general structure of the total selection index has decreased from 27 to 20%, the proportion of the component, which is due to differential fertility, has increased from 73 to 80%. Significant differences in the selection index between sub-ethnic groups of Crimean Tatars have not been identified.